2010
DOI: 10.3171/2010.3.spine09445
|View full text |Cite
|
Sign up to set email alerts
|

Radiological changes of the operated and adjacent segments following cervical arthroplasty after a minimum 24-month follow-up: comparison between the Bryan and Prodisc-C devices

Abstract: Object. The purposes of this retrospective study were to determine the radiological changes at the index and adjacent levels after cervical arthroplasty using the Bryan disc and Prodisc-C disc after a minimum 24 months followup, and to demonstrate the possible clinical factors related to these changes. Methods. Following single-level cervical arthroplasty using either the Bryan disc or Prodisc-C, the degree of facet degeneration and other radiological changes at the index and adjacent levels were assessed by o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
28
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 39 publications
1
28
0
Order By: Relevance
“…Although the data in the paper by Ryu et al 8 are interesting, this study has a number of important limitations. The strength of the conclusions is limited by the retrospective, consecutive patient design.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…Although the data in the paper by Ryu et al 8 are interesting, this study has a number of important limitations. The strength of the conclusions is limited by the retrospective, consecutive patient design.…”
mentioning
confidence: 74%
“…Ryu et al 8 should be commended for including a broad spectrum of radiographic outcome measures and trying to relate these to in vivo clinical outcomes. Should arthroplasty devices maintain pathological ROM or restore it?…”
mentioning
confidence: 99%
“…There are several theories related to the cause of HO, but none provide a satisfactory explanation of its features [9,10,16]. One report suggested that age and sex are possible risk factors for the occurrence of HO [10], other authors have reported no relationship between sex and occurrence of HO [9,16].…”
Section: Introductionmentioning
confidence: 94%
“…Most of the recent studies on HO have demonstrated an unacceptably higher occurrence rate than expected after cervical arthroplasty [1,9,16,22]. Yi et al [24] even insisted that HO after cervical disc replacement surgery is an inevitable postoperative complication, although differences in occurrence rates were observed according to the prosthesis type.…”
Section: Introductionmentioning
confidence: 97%
“…[27][28][29][30] A specific complication related to cervical disc prostheses is periprosthetic ossification. [31][32][33][34][35][36] Bone is formed around the prosthesis and can restrict movement. It is remarkable that this occurrence does not alter clinical outcome.…”
mentioning
confidence: 99%